Peripheral clearance of brain-derived Aβ in Alzheimer's disease: pathophysiology and therapeutic perspectives - Cheng, Yuan (Transl Neurodegener, 2020)
Alzheimer’s disease (AD) is the most common type of dementia, and no disease-modifying treatments are available to halt or slow its progression. Amyloid-beta (Aβ) is suggested to play a pivotal role in the pathogenesis of AD, and clearance of Aβ from the brain becomes a main therapeutic strategy for AD. Recent studies found that Aβ clearance in the periphery contributes substantially to reducing Aβ accumulation in the brain. Therefore, understanding the mechanism of how Aβ is cleared in the periphery is important for the development of effective therapies for AD. In this review, we summarized recent findings on the mechanisms of Aβ efflux from the brain to the periphery and discuss where and how the brain-derived Aβ is cleared in the periphery. Based on these findings, we propose future strategies to enhance peripheral Aβ clearance for the prevention and treatment of AD. This review provides a novel perspective to understand the pathogenesis of AD and develop interventions for this disease from a systemic approach.